Luigi Pellegrin: Visions of Infinity (diségno, 2021)
The architecture and the complex, prolific, and multifaceted figure of Luigi Pellegrin, a French-born Rome-based architect, are investigated here through some of his drawings that embody the vision of a world that does not exist but which, at the same time, appears within the reach of an evolved society. The discovery of a manuscript of notes for a lesson, accompanied by some photocompositions, and the personal memory linked to one of his unpublished drawings constitute the starting point for investigating his architecture. The authors here discuss his privilege with drawing, formed in the university lectures of Vincenzo Fasolo; the perspectival section, the main device of his project communication; and the semantic connotation that the position of the observer and the perspective structure seem to add to the reception of his projects.
Keywords: Luigi Pellegrin; perspective section; utopia; photomontage